Bevacizumab for Refractory Gastrointestinal Bleeding in Rendu-Osler-Weber Disease - Bernardes, C (2018)
Rendu-Osler-Weber disease, also known as hereditary hemorrhagic telangiectasia, is a rare autosomal dominant disorder which is often characterized by recurrent epistaxis, mucocutaneous and gastrointestinal telangiectasias, and visceral arteriovenous malformations. Patients with gastrointestinal involvement can present with a wide spectrum of severity, which may vary from uncomplicated iron deficiency anemia to continuous and refractory bleeding. We present the case of a 62-year-old female, who was admitted with anemia following several episodes of melena, and whose endoscopic examination revealed multiple angiodysplasias in the stomach and small bowel. Despite endoscopic and medical treatment attempts with hormonal agents and octreotide, she developed persistent hemorrhage and severe anemia, requiring frequent red blood cell transfusions. Immediately after initiating bevacizumab (7.5 mg/kg, every 3 weeks), complete cessation of bleeding episodes was observed. Currently, after 1 year of follow-up, she maintained sustained remission without the occurrence of adverse events.